2009
DOI: 10.2172/947896
|View full text |Cite
|
Sign up to set email alerts
|

Total Dissolved Gas Effects on Incubating Chum Salmon Below Bonneville Dam

Abstract: SummaryAt the request of the U.S. Army Corps of Engineers (USACE), Portland District, the Pacific Northwest National Laboratory (PNNL) conducted research to measure the concentration of total dissolved gas (TDG) in chum salmon (Oncorhynchus keta) spawning areas downstream of Bonneville Dam and to assess the impact of elevated dissolved gas on chum salmon survival. Spring spill at the dam occurs when chum salmon sac fry are still in the gravel. Prior to this study, no data existed on the concentration of TDG wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Therefore, if the appropriate temperatures to use in a model of emergence could be determined, the prediction of when the fish will emerge would be fairly straightforward. However, our research over the past several years in the Ives Island area suggests a large difference between river temperature and the temperature at the locations where chum salmon eggs/embryos are placed (Arntzen et al 2008a(Arntzen et al , 2009b. In the Ives Island area, there can be significant variations in riverbed temperature within a fairly small area, and this variation in temperature is a function of the spatial heterogeneity of riverbed sediments, groundwater inputs, and tailwater fluctuations (Geist et al 2002Arntzen et al 2009a).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Therefore, if the appropriate temperatures to use in a model of emergence could be determined, the prediction of when the fish will emerge would be fairly straightforward. However, our research over the past several years in the Ives Island area suggests a large difference between river temperature and the temperature at the locations where chum salmon eggs/embryos are placed (Arntzen et al 2008a(Arntzen et al , 2009b. In the Ives Island area, there can be significant variations in riverbed temperature within a fairly small area, and this variation in temperature is a function of the spatial heterogeneity of riverbed sediments, groundwater inputs, and tailwater fluctuations (Geist et al 2002Arntzen et al 2009a).…”
Section: Discussionmentioning
confidence: 79%
“…The state water quality standard used to provide protection for preemergent chum salmon rearing in the gravel has been to limit TDG to 105% after allowing for depth compensation, i.e., TDG in the river could be as high as 115% assuming three feet of water depth over the redds (NOAA 1995). The results of a 3-year study conducted from 2006 through 2008 suggested that if water depth over redds in the Ives Island area remained greater than 3 feet deep, then depth compensated TDG remained below 105% (Arntzen et al , 2008a(Arntzen et al , 2009b. However, there were times during the study when adequate depth compensation was not always provided, especially to redds spawned at relatively high riverbed elevations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations